(untitled) (Advances in Applied Mathematics and Mechanics, 2021)
The purpose of this work is to shed some light on the dynamics of the equilateral restricted four-body problem with equally massed radiating bodies. The positions along with the linear stability of the coplanar equilibria are determined by using numerical methods. Specifically, we conduct a rigorous and systematic analysis for elucidating the influence of the mass parameter m_3 and the radiation pressure factor q on the dynamics of the system. Our results indicate that these two parameters are very influential in the equilibria of the system.